BUSINESS PLAN CO-WORKING SPACE BERBASIS LAYANAN INFORMASI ILMIAH: STUDI PADA PERPUSTAKAAN PDDI LIPI KAWASAN JAKARTA - Noorika Retno Widuri; Maman Setiawan (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2021)
ABSTRACT The transformation of the library into a center of activity has been initiated in several libraries in Indonesia. Abroad, libraries as market places that provide co-working space services have begun to be implemented. This trend is in line with the increasing number of freelancers, the increasing number of business startups that do not need a permanent place to work or are nomadic. The PDDI LIPI Jakarta Library has a great opportunity to become a co-working space. As a form of support for the level of community literacy, co-working space business is not limited to work places and facilities, but is also supported by access to scientific information to support their duties and work. This paper analyzes co-working space business plans and scientific information services in the Jakarta Area library in terms of SWOT analysis, product and competitor advantages, service diversification and market segmentation, marketing plans and budgeting plans. This paper uses a descriptive method in delivering the analysis.